Numerical simulations on effects of turbulence on the size spectrum of sinking particles in ocean surface boundary layer - Nishino, Keisuke; Yoshikawa, Yutaka (Frontiers in Earth Science, 2024)
Sinking particles in the ocean play a crucial role in the climate system by transporting materials, such as carbon, deep into the ocean. The amount of this transport is influenced by the net sinking speed of the particles and the amount of material attached to them, both of which are determined by the size spectrum of the particles. The spectrum is shaped by aggregation and disaggregation processes, which are typically most active in the ocean surface boundary layer (OSBL), where intense turbulent flows can enhance both particle collision (aggregation) and particle fragmentation (disaggregation). This study aims to reveal the mechanism by which turbulence transforms the size spectrum through these competing processes and to determine whether turbulence alters the downward material transport from the OSBL. To achieve this, we performed large-eddy simulations to reproduce wind- and wave-induced turbulent flows, employing a Lagrangian particle model to track passive particles in the flow and simulate their aggregation and disaggregation. The model tracked groups of particles rather than individual ones. The results revealed that the shape of the simulated size spectrum was characterized by two length scales, the compensation radius (characterizing the particle floatability) and the Kolmogorov scale, which define the shear range where the turbulent shear shapes the spectrum, the sinking range where the gravitational sinking of particles shapes the spectrum, and the transition range between them. The findings revealed that turbulence tends to increase the terminal velocity and decrease the specific surface area of sinking particles when turbulent aggregation dominates over disaggregation, and vice versa. Although these results may be influenced by uncertain parameterizations (e.g., disaggregation parameterization), the study demonstrates the effectiveness of the numerical approach in investigating the fundamental processes governing particle sinking in turbulent flows.